Design and optimization of a bio-inspired hull shape for AUV by surrogate model technology. Issue 1 (1st January 2021) - Sun, Tongshuai; Chen, Guangyao; Yang, Shaoqiong; Wang, Yanhui; Wang, Yanzhe; Tan, Hua; Zhang, Lianhong
Abstract : This paper proposes a bio-inspired hull shape (BHS) for AUV by studying and modeling the body shape of humpback whales. Among factors affecting hydrodynamic characteristics, this paper considers both the hull drag and displacement volume to optimize the BHS, which profitably improve the space utilization and voyage of the AUV. The optimization is conducted by a surrogate model using response surface methodology (RSM), during which the translational propagation Latin hypercube design (TPLHD) is adopted to obtain sampling points. In order to verify the optimization results of BHS, the drag computations for BHS and eight typical hull shapes of existing typical or bionic AUVs are performed for comparison under conditions of similar volume, wet surface area, body length and attachments. A scaled-down model of BHS with attachments is then designed, manufactured and carried out a towing tank test. The drag measured in the towing tank test is basically the same as the simulation result, with the average relative error of 3.68% at 4m/s. The result of the shape optimization performed with the RSM is effective. Furthermore, the proposed BHS is highly suitable for underwater vehicles with requirements for longer distance, higher speed or better sensor carrying capacity.